SOEP-IS 2016 - INNO_H: Household-variables from the innovation modules - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
The File INNO contains household data from the innovative modules with one row per household and wave.
Keywords: 330